2020
DOI: 10.1155/2020/5742053
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Statistical Feature Subset Selection for Bearing Fault Detection and Severity Estimation

Abstract: The performance of bearing fault detection systems based on machine learning techniques largely depends on the selected features. Hence, selection of an ideal number of dominant features from a comprehensive list of features is needed to decrease the number of computations involved in fault detection. In this paper, we attempted statistical time-domain features, namely, Hjorth parameters (activity, mobility, and complexity) and normal negative log likelihood for Gaussian mixture model (GMM) for the first time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…As shown in Equation (38), PerEn provides a scalar value. SepEn requires the generation of a signal based on PerEn, which is calculated using a certain data window.…”
Section: Spectral Entropy Of the Permutation Entropy Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Equation (38), PerEn provides a scalar value. SepEn requires the generation of a signal based on PerEn, which is calculated using a certain data window.…”
Section: Spectral Entropy Of the Permutation Entropy Signalmentioning
confidence: 99%
“…The kurtosis, covariance, root mean square (RMS), and skewness are indicators that are widely used in the literature [ 34 , 35 ]. In addition, other indicators have been developed in the time domain, such as factors [ 36 , 37 , 38 ], and Hjorth parameters [ 39 , 40 , 41 ]. In the frequency domain, several statistical indicators have their counterparts from the time domain, which are helpful for frequency analysis [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 Earlier, these parameters were more common in biomedical fields, 34 however, with recognized potential of fault characterization, the Hjorth's parameters have been successfully applied in some of the recent research works. [35][36][37][38][39][40][41] Caesarendra and Tjahjowidodo 35 studied the changes in statistical features, including Hjorth's parameters, as the natural fault develops in slow speed slew bearings, and found that impulse factor, margin factor, approximate entropy and largest Lyapunov exponent possess the fault indicative potentials. Among Hjorth's three parameters, only activity was found sensitive to the occurrence of fault.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wan et al [ 23 ] compared the performance of different inputs in their research by using eight distinct types of inputs namely STFT, Constant-Q Gabor Transform, Instantaneous Frequency, Fast Kurtogram, HHT, Wigner–Ville Distribution, Fourier Synchro-squeezed Transform (FST), and CWT. Other academics have used statistical features for rotating machinery diagnostic systems [ 24 , 25 , 26 , 27 , 28 ]. Although the performance of fault diagnosis systems depends on the feature spaces used [ 28 ], it was observed that these feature spaces were used arbitrarily and not combined in such a way to achieve generalization between different conditions, that the bearings may be subjected.…”
Section: Introductionmentioning
confidence: 99%
“…Other academics have used statistical features for rotating machinery diagnostic systems [ 24 , 25 , 26 , 27 , 28 ]. Although the performance of fault diagnosis systems depends on the feature spaces used [ 28 ], it was observed that these feature spaces were used arbitrarily and not combined in such a way to achieve generalization between different conditions, that the bearings may be subjected. For instance, in [ 9 ] while the FFT would give unsatisfactory results with a signal whose frequency components changes with time, the wavelet transform is known to suffer from fixed scale resolution which would affect its real-life applications, and the HHT suffers from instability in its signal decomposition process.…”
Section: Introductionmentioning
confidence: 99%